Serological detection of viruses included in certification protocols for stone fruits - Boscia D.; Myrta A. (Stone fruit viruses and certification in the Mediterranean countries: problems and prospects, 1998)
Stone fruits are affected by many viruses which are routinely detected by serological methods. The paper focuses on ELISA and other serological techniques reviewing reports for Trichoviruses, Potyviruses, Ilarviruses, and Nepoviruses affecting stone fruits. Diagnostic problems that disturb the reliability of ELISA results are also discussed.